Characterization of Essential Oils and Fatty Acids Composition of Stored Ginger (Zingiber officinale Roscoe) - C.C. Oforma; G.A. Udourioh; C.M. Ojinnaka (Journal of Applied Sciences and Environmental Management)
The essential oils and fatty acids composition of stored Zingiber officinale Roscoe (Ginger) were characterized using Gas chromatographic-Mass Spectrometric (GC/MS) method. The ginger rhizomes sample was procured from spices store at Bwari main market, Abuja, Nigeria. It was pretreated and the proximate analysis was carried out. The essential oils and fatty acids were extracted using Hydro-distillation unit. It was then analyzed using GC/MS. From the results obtained, the proximate composition showed 8.50% protein content, 3.80% crude fibre, 5.10% fat, 3.60% ash content, 10.20% moisture and 68.80% carbohydrate content. 38 essential oil components were found and the essential oil was dominated by the compound class Sesquiterpenes (64.83%) followed by Esters (13.29%), aldehydes (9.16%), Sesquiterpenols (6.46%) and monoterpenes (5.71%). Monoterpenols constituted 3.35% while ketones and oxides were seen in trace amounts. The specific dominant constituents were zingiberene (28.57%), Arcurcumene (14.22%) and Geranyl Acetate (13.28%). There was a decrease in the number of sesquiterpenes and monoterpenes in the stored ginger compared to the number earlier reported on freshly harvested and dried samples but the reduction did not affect the overall average percentage composition. The fatty acid comprised 50% saturated acids and 50% unsaturated acids and was dominated by Linoleic Acid (23.92%)  followed by palmitic acid (22.18%), oleic acid (20.40%) and Lauric Acid (8.34%). The composition of the Zingiber officinale essential oil and fatty acid has shown that the plant contains true essential oils, implying that the medicinal and flavouring strength of the plants may be attributed to its essential oil composition.